Cultivating Responsibilities of Vocational Teachers: A Framework for Preparing Education to Work - Didik Nurhadi; Nyan-Myau Lyau (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
Vocational education is responsible for preparing the needs of a global workforce to develop the country's economy. understand the role of vocational education to work properly. The question that arises is how to cultivate their responsibilities for preparing vocational education to work? The solution offered is a framework to prepare vocational education to work. This understanding is bringing education to be able to follow the manpower needs in accordance However, issues of vocational education in developing countries are a lack of link and match between education and industry, lack of relevant skills of graduates with the needs of industry owners, the lack of quality, competencies, and professionalism of vocational teachers. The quality of teachers affects the quality of students' skills so that vocational teachers need to with local and global trends. Furthermore, using a literature review, steps to cultivate teacher's responsibilities were discussed in this paper. Finally, this framework grows teachers' quality in order to support state economic development.